Desenvolvimento das células espermáticas do caranguejoaratu, Goniopsis cruentata Latreille, 1803 (Crustacea: Decapoda: Grapsidae) - Garcia, Tatiane Martins (2009)
The red-clawed mangrove-tree crab, Goniopsis cruentata, constitutes an important economic resource in Northeastern Brazil. Male specimens were collected and submitted to histological routine tests. Four types of sperm cell were observed in the anterior region of the testis: spermatogonia, spermatocytes, spermatids and spermatozoa. The general development of sperm cells in G. cruentata follows the basic pattern described for decapods. To our knowledge, no description of sperm cell development in G. cruentata has been published previously